Immovable property tax administration in Kumasi metropolis. Prospects and challenges - Acquah-Ababio, Ama Serwaa (KNUST, 2025)
A thesis presented to the department of planning in partial fulfilment of the requirement for the award Of Master of Development Policy and Planning